Motor cortex activity during action observation predicts subsequent action imitation in human infants - Köster, Moritz; Langeloh, Miriam (NeuroImage, 2020)
From early on, human infants acquire novel actions through observation and imitation. Yet, the neural mechanisms that underlie infants’ action learning are not well understood. Here, we combine the assessment of infants’ neural processes during the observation of novel actions on objects (i.e. transitive actions) and their subsequent imitation of those actions. Most importantly, we found that the 7-10 ​Hz motor cortex activity increased during action observation and predicted action imitation in 20-month-olds (n ​= ​36). 10-month-olds (n ​= ​42), who did not yet reliably imitate others’ actions, showed a highly similar neural activity pattern during action observation. The presence or absence of communicative signals did neither affect infants’ neural processing nor their subsequent imitation behavior. These findings provide first evidence for neural processes in the motor cortex that allow infants to acquire transitive actions from others ‒ and pinpoint a key learning mechanism in the developing brain of human infants.